2020
DOI: 10.1016/j.waojou.2020.100477
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of risk factors associated with atopic dermatitis in Asia

Abstract: Background Atopic dermatitis (AD) is a chronic, inflammatory skin disorder characterised by intense itch and eczematous lesions. Rising prevalence of AD has been observed worldwide including in Asia. Understanding the risk factors associated with AD may explain its pathogenicity and identify new preventive strategies and treatments. However, AD-associated risk factors and comorbidities specific to Asia have not been systematically reviewed. Methods We performed a system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 84 publications
1
42
1
Order By: Relevance
“…One of the studies cited above notes substantial differences in three Asian cities, with higher prevalence of AD coinciding with increased levels of urbanization [12]. This observaton was also supported in a recent metaanalysis which showed that urbanization in addition to maternal and personal history of smoking were the strongest environmental factors correlating with AD among Asians [21]. There is also basic science supporting this concept, with a potential link between pollution and AD found in the aryl hydrocarbon receptor [22].…”
Section: Discussionmentioning
confidence: 81%
“…One of the studies cited above notes substantial differences in three Asian cities, with higher prevalence of AD coinciding with increased levels of urbanization [12]. This observaton was also supported in a recent metaanalysis which showed that urbanization in addition to maternal and personal history of smoking were the strongest environmental factors correlating with AD among Asians [21]. There is also basic science supporting this concept, with a potential link between pollution and AD found in the aryl hydrocarbon receptor [22].…”
Section: Discussionmentioning
confidence: 81%
“…AD is a chronic inflammatory disease of the skin characterized by eczematous lesions and a sensation of intense itching. It originates from alteration of the integrity of the epidermal barrier as a consequence of the interaction between genetic and environmental factors [ 99 , 100 , 101 , 102 ]. Due to skin barrier defects, there is an increase in the permeability to antigens, both of chemical and protein nature.…”
Section: Participation Of Keratinocyte In Predisposition Onset and Progression Of The Atopic Dermatitismentioning
confidence: 99%
“…It is worsening in nature, often with recurrent burns, and can perhaps negatively affect the quality of life in affected individuals. A recent epidemiological and meta-analysis study suggests that atopic eczema is genetic-based along with primary causes of external environments, including, smoking [4]. The prevalence of eczema occurs in all age groups; however, it significantly appears during childhood [5].…”
Section: Targeting Eczema Treatment By Clearing the Liver Heat And Detoxification: A Clinical Case Reportmentioning
confidence: 99%